Physical Properties Investigation on Sunscreens with Red Dragon Fruit Peel Extract - Ruth Febriana Kesuma; Rokiy Alfanaar; Markus Angkawijaya (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2023)
Red dragon fruit peel extract is reported as an active ingredient in sunscreen because of its ability to protect the skin. UV exposure to the skin can cause reddish skin to develop skin cancer. This study aimed to determine the characteristics of the cream made from ZnO and red dragon fruit peel extracts (Hylocereus costaricensis), such as sun protection factor (SPF), pH, stability, viscosity, spreadability, and adhesion. Red dragon fruit peel extract was obtained by maceration using methanol, and DPPH-scavenging activity resulted in an IC50 of 0.96 μg/mL. Measurement of diffuse UV-vis reflectance shows that ZnO has absorption at λex 385 nm, which correlates with a bandgap energy of 3.22 eV. F1 formulation cream (red dragon fruit peel extract and ZnO ratio of 0:1) has the highest SPF value of 17. The Kruskal-Wallis test shows that there is a significant difference in adhesion between the F1 formulation cream with F2 (p-value = 0.002) and F4 (p-value = 0.03).